Venocentric Lesions: An MRI Marker of MS? - Quinn, Matthew P.; Kremenchutzky, Marcelo; Menon, Ravi S. (Frontiers in Neurology, 2013)
From the earliest descriptions of MS, the venocentric characteristic of plaques was noted. Recently, numerous MRI studies have proposed this finding as a prospective biomarker for MS, which might aid in differentiating MS from other diseases with similar MRI findings. High field MRI studies have shown that penetrating veins can be detected in most MS lesions using T2* weighted or susceptibility weighted imaging. Future studies must address the feasibility of imaging such veins in a clinically practical context. The specificity of this biomarker has been studied only in a limited capacity. Results in microangiopathic lesions are conflicting, whereas asymptomatic white matter hyperintensities as well as lesions of NMO are less frequently venocentric compared to MS plaques. Prospective studies have shown that the presence of venocentric lesions at an early clinical presentation is highly predictive of future MS diagnosis. This is very promising, but work remains to be done to confirm or exclude lesions of common MS mimics, such as ADEM, as venocentric. A number of technical challenges must be addressed before the introduction of this technique as a complementary tool in current diagnostic procedures.